(untitled) (Universal International Scientific Journal, 2026)
This article studies the effects of different plant densities and application of sojean growth regulator on plant dry mass accumulation during the squaring phase of long staple cotton using drip irrigation and a double row planting scheme in soil-climatic conditions of Surkhandarya region, southern zone of Uzbekistan.